DEVELOPMENT OF STEM BASED E-MODULES ABOUT SOCIOSCIENTIFIC ISSUES THE EAST KALIMANTAN TROPICAL RAINFOREST - Erna Suhartini; Rosita Putri Rahmi Haerani (EDUSAINS, 2022)
The aim of this study is to create STEM-based science e-modules contains East Kalimantan-specific concepts, such as habitats, ecosystems, resource use, environmental pollution, and fauna conservation. In addition, this research also evaluates how students’ response as user to the use of e-modules. This study uses the Borg and Gall research and development (RnD) model, which is only applicable to the main product revision stage in this paper. Student answer questionnaires, material and media expert validation sheets were the instruments utilized in this investigation. Three experts who taught the discipline of biology education and computer education validated the work of material and media specialists. According to the validators' evaluation, the final module is valid and very testable, with the average percentage of media expert review is 97.62%. and content expert review is 87.50%. 11 students from the Elementary School Teacher Education Study Program, FKIP, Mulawarman University, participated in the e-module trial phase. According to the answer questionnaire, the created e-module received a positive response with an average percentage of 90.77%, placing it in the satisfactory range and making It is safe for use as a learning resource in the instructional process.AbstrakTujuan dari penelitian adalah untuk mengembangkan e-modul STEM (Science, Technology, Engineering, Mathematic) pada beberapa topik tertentu meliputi habitat, ekosistem, pemanfaatan sumber daya alam, pencemaran lingkungan dan konservasi fauna khas kalimantan timur, dan menemukan dampak e-modul pada respon penggunanya yaitu mahasiswa. Penelitian ini menggunakan paradigma pengembangan Borg and Gall, yang merupakan jenis penelitian dan pengembangan (R&D) yang kami batasi hanya sampai pada tahap 5 yakni tahap revisi produk. Kuesioner tanggapan pengguna, lembar validasi ahli materi dan media digunakan dalam pengambilan data penelitian. Validasi pakar materi dan media dilakukan oleh 3 orang pakar yang merupakan dosen prodi pendidikan biologi dan pendidikan komputer. Berdasarkan penilaian para pakar selaku validator, modul akhir dinyatakan valid dan sangat dapat diuji coba skala besar, dengan rata-rata persentase dari pakar media sebesar 97,62%. Pakar pada materi juga menyatakan rerata persentase yang tinggi yaitu 87,50%. Sebelas mahasiswa dari Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Mulawarman, mengikuti tahap uji coba kelompok kecil e-modul. Berdasarkan angket respon pengguna, e-modul yang dibuat mendapat respon yang sangat positif dengan persentase rata-rata 90,77%, sehingga diputuskan layak untuk digunakan sebagai sumber belajar dalam proses pembelajaran.How To Cite: Suhartini, E., Haerani, R.P.R. (2022). Development Of STEM Based E-Modules About the East Kalimantan Tropical Rainforest. EDUSAINS, 14 (2) : 137-147